Penerapan Segmentasi Pelanggan dengan Menggunakan Metode K-Means Clustering Pada Sistem Customer Relationship Management di PT. Titess - Michael Boentarman; Silvia Rostianingsih; Alexander Setiawan (Jurnal Infra, 2021)
PT. Titess is a consumer good company with a variety of products such as consumption salt, packaged cooking oil, soap, sugar and so on. Currently PT. Titess has distributors whose role is to market products directly to consumers. With the aim of increasing sales at each distributor, PT. Titess provides special treatment. Special treatment is given manually for certain distributors. This is felt to be less than optimal, because the special treatment given is not right on target for each distributor who has the most sold superior product types. Therefore, we need a distributor segmentation system using the K-means method referring to sales history data. The proposed system also has features that can help distributors to place orders independently, confirm payments, submit returns, submit complaints and exchange reward points for prizes that can be arranged by the company. The results of the system have been tested for system acceptance using a questionnaire that was distributed to 5 users. The results of the system acceptance test show the distributor's satisfaction level with the system. Distributors feel the convenience and benefits of the system.